Endogenous Glutamate Excites Myenteric Calbindin Neurons by Activating Group I Metabotropic Glutamate Receptors in the Mouse Colon - Swaminathan, Mathusi; Hill-Yardin, Elisa L.; Bornstein, Joel C.; Foong, Jaime P. P. (Frontiers in Neuroscience, 2019)
Glutamate is a classic excitatory neurotransmitter in the central nervous system (CNS), but despite several studies reporting the expression of glutamate together with its various receptors and transporters within the enteric nervous system (ENS), its role in the gut remains elusive. In this study, we characterized the expression of the vesicular glutamate transporter, vGluT2, and examined the function of glutamate in the myenteric plexus of the distal colon by employing calcium (Ca2+)-imaging on Wnt1-Cre; R26R-GCaMP3 mice which express a genetically encoded fluorescent Ca2+ indicator in all enteric neurons and glia. Most vGluT2 labelled varicosities contained the synaptic vesicle release protein, synaptophysin, but not vesicular acetylcholine transporter, vAChT, which labels vesicles containing acetylcholine, the primary excitatory neurotransmitter in the ENS. The somata of all calbindin (calb) immunoreactive neurons examined received close contacts from vGluT2 varicosities, which were more numerous than those contacting nitrergic neurons. Exogenous application of L-glutamic acid (L-Glu) and N-methyl-D-aspartate (NMDA) transiently increased the intracellular Ca2+ concentration [Ca2+]i in about 25% of myenteric neurons. Most L-Glu responsive neurons were calb immunoreactive. Blockade of NMDA receptors with APV significantly reduced the number of neurons responsive to L-Glu and NMDA, thus showing functional expression of NMDA receptors on enteric neurons. However, APV resistant responses to L-Glu and NMDA suggest that other glutamate receptors were present. APV did not affect [Ca2+]i transients evoked by electrical stimulation of interganglionic nerve fibre tracts, which suggests that NMDA receptors are not involved in synaptic transmission. The group I metabotropic glutamate receptor (mGluR) antagonist, PHCCC, significantly reduced the amplitude of [Ca2+]i transients evoked by a 20 pulse (20 Hz) train of electrical stimuli in L-Glu responsive neurons. This stimulus is known to induce slow synaptic depolarizations. Further, some neurons that had PHCCC sensitive [Ca2+]i transients were calb immunoreactive and received vGluT2 varicosities. Overall, we conclude that electrically evoked release of endogenous glutamate mediates slow synaptic transmission via activation of group I mGluRs expressed by myenteric neurons, particularly those immunoreactive for calb.